A Study of Islamic Moderation Discourse Among Female Scholars in Banyumas Regency Based on Their Interpretation of Radical-Indicating Hadiths - Munawir, Munawir; Liddini, Laily; Arjuna, Klawing (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Islamic radicalism in Indonesia has evolved from merely an ideology to a full-blown terrorist movement. In the context of the spread of Islamic radicalism in Indonesia, Banyumas Regency is categorized as a yellow zone, signifying it is under surveillance by Densus 88 and BNPT. Islamic radicalism is triggered by numerous factors, with one of the primary causes being a textualistic and non-comprehensive understanding of religious texts, including hadith. Particularly problematic are hadith with radical connotations. Islamic scholars play a crucial role in deradicalization discourse. Traditionally, Islamic scholars have been associated with the male gender; however, there are now many female scholars whose Islamic thought contributes significantly and is accessible to the public, including female scholars in Banyumas Regency. Through fieldwork involving observation, interviews, and document analysis, and subsequent data analysis using theories of textualist and contextualist understanding and Islamic moderation, it was found that female scholars in Banyumas Regency interpret hadith with radical connotations contextually and possess moderate Islamic thought and practices.